Circulating tumor DNA predicts efficacy of a dual AKT/p70S6K inhibitor (LY2780301) plus paclitaxel in metastatic breast cancer: plasma analysis of the TAKTIC phase IB/II study. Issue 10 (30th March 2022) - Sabatier, Renaud; Vicier, Cécile; Garnier, Séverine; Guille, Arnaud; Carbuccia, Nadine; Isambert, Nicolas; Dalenc, Florence; Robert, Marie; Levy, Christelle; Pakradouni, Jihane; Adelaïde, José; Chaffanet, Max; et al.
Abstract : The phosphatidylinositol‐3‐kinase (PI3K)/AKT/mammalian target of rapamycin (mTOR) pathway is frequently activated in HER2‐negative breast cancer and may play a role in taxane resistance. The phase IB/II TAKTIC trial (NCT01980277) has shown that combining a dual AKT and p70 ribosomal protein S6 kinase (p70S6K) inhibitor (LY2780301) taken orally with weekly paclitaxel in HER2‐negative advanced breast cancer is feasible, with preliminary evidence of efficacy. We wanted to explore whether circulating tumor DNA (ctDNA) may be a surrogate marker of treatment efficacy in this setting. Serial plasma samples were collected and cell‐free DNA was sequenced using low‐coverage whole‐genome sequencing, and analysis was completed with droplet digital polymerase chain reaction (PCR) for some patients with driver mutations. Baseline tumor fraction (TF) and TF after 7 weeks on treatment were compared to progression‐free survival (PFS) and the overall response rate. We also explored circulating copy number alterations associated with treatment failure. Of the 51 patients enrolled in the TAKTIC trial, at least one plasma sample was available for 44 cases (96 timepoints). All patients with tumor TP53, PI3KCA, or AKT1 mutations harbored at least one of these alterations in plasma. TF at inclusion was correlated with PFS (6m‐PFS was 92% for ctDNAneg patients vs 68% for ctDNApos cases; hazard ratio [HR] = 3.45, 95% confidence interval [CI] [1.34–8.90], P = 0.007). ctDNA status at week 7 was not correlated with prognosis. Even though most circulating copy number alterations were conserved at disease progression, some genomic regions of interest were altered in post‐progression samples. In conclusion, ctDNA detection at baseline was associated with shorter PFS in patients included in the TAKTIC trial. Plasma‐based copy number analysis may help to identify alterations involved in resistance to treatment. Abstract : We used whole‐genome sequencing of circulating tumor DNA (ctDNA) to obtain copy number alteration profiles from the plasma of patients with metastatic breast cancer receiving a combination of paclitaxel and LY2780301 (dual AKT/p70S6H inhibitor). ctDNA detection at baseline predicted shorter progression‐free survival. Post‐progression plasma copy number alteration analysis may identify genomic alterations involved in resistance to treatment.